Design and synthesis of chiral and regenerable [2.2]paracyclophane-based NAD(P)H models and application in biomimetic reduction of flavonoids. Issue 37 (15th September 2020) - Zhu, Zhou-Hao; Ding, Yi-Xuan; Wu, Bo; Zhou, Yong-Gui
Abstract : With the rapid development of biomimetic asymmetric reduction, the demand for efficient chiral and regenerable NAD(P)H models is growing rapidly. Abstract : With the rapid development of biomimetic asymmetric reduction, the demand for efficient chiral and regenerable NAD(P)H models is growing rapidly. Herein, a new class of [2.2]paracyclophane-based chiral and regenerable NAD(P)H models (CYNAMs) was designed and synthesized. The first enantioselective biomimetic reduction of tetrasubstituted alkene flavonoids has been successfully realized through enzyme-like cooperative bifunctional activation, giving chiral flavanones with up to 99% yield and 99% ee.